Incorporation of 3D stereophotogrammetry as a reliable method for assessing scar volume in standard clinical practice. Issue 7 (November 2019) - Peake, Mitchell; Pan, Kristen; Rotatori, R. Maxwell; Powell, Heather; Fowler, Laura; James, Laura; Dale, Elizabeth
Highlights: 3D photography provides accurate assessment of burn scar volume. A 3D camera is a practical tool for use in clinical practice. Scars may be objectively followed over time with 3D photography. Abstract: Significant disfigurement and dysfunction is caused by hypertrophic scarring, a prevalent complication of burn wounds. A lack of objective tools in the assessment of scar parameters makes evaluation of scar treatment modalities difficult. 3D stereophotogrammetry, obtaining measurements from 3D photographs, represents a method to quantitate scar volume, and a 3D camera may have use in clinical practice. To validate this method, scar models were created and photographed with a 3D camera. Measurements from 3D image analysis of these scar models were compared to physical measurements of scar model volume. Reliability of 3D image analysis was assessed with both scar models and burn patient scars. Measurements of scar models by two independent observers were compared to determine inter-rater reliability, and measurements from 3D images of burn patient hypertrophic scars were compared to determine the consistency of the method between observers. The time taken for patient photography was recorded. No significant differences were found between the two methods of volume calculation (p = 0.89), and a plot of the differences showed agreement between the methods. The correlation coefficient between the two observers' measurements of scar model volume was 0.92, and the intra-class correlation coefficient for patient scar volume was 0.998, showing good reliability. The time required to capture 3D photographs ranged from 2 to 6 min per patient, showing the potential for this tool to be efficiently incorporated into clinical practice. 3D stereophotogrammetry is a valid method to reliably measure scar volume and may be used to objectively measure efficacy of scar treatment modalities to track scar development and resolution.